2022
DOI: 10.1055/a-1914-1722
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Tandem Cyclization of Alkynes with Phenylsulfinic Acids: Access to Sulfone-Substituted Dioxodibenzothiazepines or Dibenzazepines

Abstract: Photoinduced tandem cyclization of alkynes with phenylsulfinic acids has been accomplished, which gives a mild strategy for the preparation of sulfone-substituted seven-membered N-heterocycles. A variety of scaled-up experiments, further trans-formations, and mechanistic studies were also operated in the follow-up work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…The detailed protocol for the preparation of the substrates is according to refs , and in the manuscript, respectively. Meanwhile, the detailed physical data of the starting material 1-s of product 1 were described as follows:…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The detailed protocol for the preparation of the substrates is according to refs , and in the manuscript, respectively. Meanwhile, the detailed physical data of the starting material 1-s of product 1 were described as follows:…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, dibenzazepines and dioxodibenzothiazepines as common 7-membered N -heterocycles have broadly existed in natural products, pharmaceuticals, and biotechnology . A series of above-medium cycles have been efficiently prepared by Li, Xu, Zhong, Wang, and other groups (Scheme a). , Meanwhile, our group also reported some photo- or persulfate-initiated tandem cyclization to access SCN/SCF 3 /ArSO 2 -revised 7-membered heterocycles (Scheme b) . As one of our study issues, we speculated whether cyanomethylated dibenzazepine and dioxodibenzothiazepines could be produced by using bromoacetonitrile as the cyano source.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…18 Furthermore, Xu, Li, and Zhong et al have reported an electrochemical or photocatalytic radical cyclization of alkynes to access diverse functionalized seven-membered dibenzazepines, which are another class of core scaffolds in many biologically active molecules. 19 Despite these achievements, the known methods have some limitations such as the requirement of stoichiometric transition-metal catalysts, expensive photocatalysts or high temperatures. To date, convenient and practical protocols for the synthesis of dioxodibenzothiazepines are still relatively limited.…”
Section: Introductionmentioning
confidence: 99%